Effect of Different Moisture Conditions on Growth and Yield Attributes of Potato Varieties Grown in Lalitpur District, Nepal - Bhattarai, Prakash; Chaudhary, Duryodhan (Nepalese Horticulture, 2024)
Field experiments were conducted in 2015 and 2016 at Hattiban Research Farm of the National Potato Research Programme (NPRP), Khumaltar, Lalitpur (1360 masl), Nepal, to investigate the effect of varying moisture conditions on the growth, yield and quality attributes of potato varieties. The experiment was set up on sandy loam soil using a split-plot design (SPD) with three replications and included six potato varieties (Cardinal, Desiree, Kufri Jyoti, Khumal Seto-1, Janakdev and Khumal Upahar) and three moisture conditions (Irrigated, Rainfed and Drought (black plastic mulch). The results revealed that moisture conditions and potato varieties significantly influence growth, tuber yield and quality traits. Plants subjected to drought conditions with plastic mulch exhibited the tallest height (62.18 cm) and higher tuber yield (36.23 t ha-1) but lower tuber number per plant (9.84) compared to irrigated conditions (11.35). Khumal Seto-1 had the highest mean number of tubers per plant (14.71) and intermediate tuber weight (0.498 kg), while Khumal Upahar had the highest tuber yield (35.43 t ha-1) followed by Kufri Jyoti (34.8. t ha-1). Khumal Upahar had the highest specific gravity (1.072) and dry matter (22.87%), while Kufri Jyoti had the lowest (1.059) and (20.26 %) among the varieties. Varieties such as Khumal Upahar, Khumal Seto-1 and Janakdev, which exhibited enhanced growth and yield under drought conditions, could be prioritized for cultivation in water scarce regions. The application of plastic mulch may be explored as a means of reducing the adverse impacts of drought on potato growth and yield. These results help potato growers enhance production and quality in varied environments. Farmers or stakeholders may work to improve potato productivity and ensure food security in the Lalitpur condition of Nepal or similar potato-growing regions by incorporating these findings into agricultural practices.